A Model‐Based Illustrative Exploratory Approach to Optimize the Dosing of Peg‐IFN/RBV in Cirrhotic Hepatitis C Patients Treated With Triple Therapy. (30th December 2014) - Laouénan, C; Guedj, J; Peytavin, G; Nguyen, TH Tram; Lapalus, M; Khelifa‐Mouri, F; Boyer, N; Zoulim, F; Serfaty, L; Bronowicki, J‐P; Martinot‐Peignoux, M; Lada, O; et al.
Abstract : Hézode et al . recently reported the frequent occurrence of anemia and thrombocytopenia in the ANRS‐CO20‐CUPIC cohort of hepatitis C virus (HCV) cirrhotic experienced patients treated with pegylated‐interferon (Peg‐IFN), ribavirin (RBV), and telaprevir or boceprevir. 1, 2 Using frequent measurements of serum drug concentrations, hemoglobin, and platelet concentrations obtained in 15 patients of this cohort, we show how an on‐treatment model‐based approach could be used to individualize dose regimen and avoid the occurrence of RBV‐induced anemia and Peg‐IFN‐induced thrombocytopenia. CPT Pharmacometrics Syst. Pharmacol. (2015) 4, 37–40; doi:10.1002/psp4.8 ; published online on 30 December 2014.